Study protocol for a randomised controlled trial examining the effect of blood and plasma donation on serum perfluoroalkyl and polyfluoroalkyl substance (PFAS) levels in firefighters. Issue 5 (7th May 2021) - Silver, Gabriel; Krastev, Yordanka; Forbes, Miriam K; Hamdorf, Brenton; Lewis, Barry; Tisbury, Michael; Taylor, Mark P; Gasiorowski, Robin
Abstract : Introduction: Perfluoroalkyl and polyfluoroalkyl substances (PFAS) are a diverse group of compounds that have been used in hundreds of industrial applications and consumer products including aqueous film-forming foam (AFFF) for many years. Multiple national and international health and environmental agencies have accepted that PFAS exposures are associated with numerous adverse health effects. Australian firefighters have been shown to have elevated levels of PFAS in their blood, specifically perfluorooctane sulfonic acid (PFOS) and perfluorohexane sulfonic acid (PFHxS), due to the historical use of AFFF. While PFAS concentrations decline over time once the source of exposure has been removed, their potential adverse health effects are such that it would be prudent to develop an intervention to lower levels at a faster rate than occurs via natural elimination rates. Methods and analysis: This is a randomised controlled trial of current and former Australian firefighters in the Metropolitan Fire Brigade/Fire Rescue Victoria, and contractors, with previous occupational exposure to PFAS and baseline elevated PFOS levels. The study is investigating whether whole blood donation every 12 weeks or plasma donation every 6 weeks will significantly reduce PFAS levels, compared with a control group. We have used covariate-adaptive randomisation to balance participants' sex and blood PFAS levels between the three groups and would consider a 25% reduction in serum PFOS and PFHxS levels to be potentially clinically significant after 12 months of whole blood or plasma donation. A secondary analysis of health biomarkers is being made of changes between screening and week 52 in all three groups. Ethics and dissemination: This trial has been approved by Macquarie University Human Research Ethics Committee (reference number: 3855), final protocol V.2 dated 12 June 2019. Study results will be disseminated via peer-reviewed publications and presentations at conferences. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12619000204145).